Description of Effective Learning Strategies for Phase F Blind Students in Exceptional Schools - Andi Nurshiddiq Ma’fud; Masri Kudrat Umar; I Made Hermanto (Universitas Muhammadiyah Palu, 2026)
This study aims to describe effective learning strategies for blind Phase F students at SLBN Gorontalo City, especially in constructing concept understanding in subjects with high levels of complexity such as Physics. The focus of this research is the implementation of the Independent Curriculum and the use of adaptive media in accommodating students' visual barriers. The method used is descriptive qualitative research with data collection techniques through non-participatory observation, in-depth interviews with teachers and students, and documentation. The results of the study show that an effective learning strategy for Phase F blind students is a multisensory approach that integrates the senses of touch (tactile) and auditory (auditory). The use of tactile media, such as embossed props and Braille systems, has been proven to be able to transform abstract concepts into concrete experiences so that they are easier to understand independently by students. In addition, the role of teachers as facilitators in designing inclusive and flexible learning according to the principles of the Independent Curriculum is an important factor in the success of learning. These findings confirm that the independence and higher order thinking skills of blind students can be optimized through the modification of media and methods that suit their sensory characteristics. This study recommends the development of more innovative tactile-based physics teaching aids to support the achievement of competencies in Phase F.